The Effect of Concept Achievement on Critical Thinking and Creative Mathematical In Elementary School Students - Iis Marwati; Moh. Uzer Usman; Tri Dyah Prastiti (Journal Research of Social Science, Economics, and Management, 2023)
This research aims to describe the effect of applying the concept achievement learning model on the ability to think critically and creatively in elementary school student. Students' capacity for original thought allows them to come up with solutions to mathematical issues in a variety of ways. This research was conducted in 6th grade at UPI Cibiru Laboratory Elementary School in the 2021–2022 academic year on cubes and blocks lessons. This research used a quasi-experimental approach with a single experimental group. There were 22 students who made up the experimental group. The selection of purposive sampling led to the creation of the class group. The independent variable in this study is the achievement of the concept, while the dependent variable is the ability to think critically and creatively. The research design used is the Nonequevalent Posttest-Only Control Group Design. The instruments used in this research are test and non-test. The test is in the form of questions to determine the effect of students' critical and creative mathematical thinking skills between those using the Concept Achievement learning model and the Inquiry Learning Model. The non-test is in the form of a Likert scale to measure students' self-confidence. The data analysis technique used prerequisite tests, namely the normality test, homogeneity test, and the average difference test. Furthermore, the correlation test uses the Pearson or Spearman test and the coefficient of determination.